PROSEDUR PELAYANAN SURAT KETERANGAN DOMISILI USAHA DI KELURAHAN PENJARINGANSARI MELALUI SURABAYA SINGLE WINDOW - Ahmat Rofpi; Katerina Bataha (Jurnal PubBis, 2024)
The government has a fundamental obligation to fulfill essential public service needs. In the era of reform, online service access is important so that people can expect quality services. Surabaya, as the second-largest city after DKI Jakarta, is experiencing rapid business growth. Therefore, every Surabaya resident is required to obtain a license as a sign of legality for individuals or businesses. The main focus of this research is to understand the procedure of handling the service of business domicile certificates in Penjaringansari Village through Surabaya Single Window, as well as to identify the inhibiting and supporting factors related to the procedure of handling the service of business domicile certificates in Penjaringansari Village through Surabaya Single Window. This research adopts a case study approach using a descriptive qualitative research method. Data collection was carried out through interviews with four informants determined by purposive sampling, observation, and documentation. The result of the research in this article is that the procedure for applying for a business domicile certificate service in Penjaringansari Village has been running in accordance with the standard operating procedures that have been determined. The inhibiting factor encountered by researchers in the procedure for handling business domicile certificate services is that the human resources (HR) in Penjaringansari Village are still minimal because there is only one officer who understands the requirements and flow of licensing on the SSW page, and there is a lack of public awareness to seek information about licensing services through the Surabaya Single Window. As well as supporting factors in business domicile certificate service procedures, which include the existence of clear laws and the suitability of officers who handle them with standard operating procedures (SOPs) that have been determined. Keywords: Public Service, Surabaya Single Window, licensing